Immunomodulatory Activity of Methanol Leaf Extract of Neem (Azadirachta indica Juss) Against Suppressor and Proinflammatory Molecules - Supriyanto, Supriyanto; Widjanarko, Simon Bambang; Rifa'i, Muhaimin; Yunianta, Yunianta (Journal of Tropical Life Science, 2021)
Neem plant is rich in bioactive constituents, which make it massively discussed the treatment of various diseases. A study on the immunomodulatory activities of neem is given here. This current work aimed to investigate the effects of neem leaf extract on immunocompetent cells. In vivo experiment was carried out using mice (Mus musculus) Â induced with DMBA, comprising positive control, negative control, and treatments of neem leaf extracts (250, 500, and 1000 ppm). Data obtained from flow cytometric analysis were evaluated using BD Cellquest ProTM software, then statistically analyzed in SPSS version 21. Parametric analysis in one-way ANOVA was performed at a significance level of 5%. The significant difference was compared in the Duncan test. The results showed that administration of neem leaf extracts significantly affected the expression of CD4+, CD8+, CD25+, CD62L, IL-10, and IL-17 cells .Neem leaf extract has immunomodulatory activities by increasing pressure molecules and decreasing pro-inflammatory molecules